Answer:
Explanation:
To simplify the given Boolean algebra expression, we can use Boolean algebra rules such as De Morgan's laws, distributive law, and complementation law.
Let's simplify step by step:
1. Apply De Morgan's law to the third term (ABC):
ABC = (A' + B' + C')
2. Apply the distributive law to the first and second terms:
AB'C + A'B'C = (A + A')B'C
3. Simplify the expression:
(A + A')B'C = 1B'C = B'C
4. Apply the distributive law to the result from step 3 and the third term:
B'C + (A'BC') = B'C + (A' + B' + C')
5. Simplify the expression:
B'C + (A' + B' + C') = B'C + 1 = B'C
Therefore, the simplified form of the Boolean algebra expression AB'C + A'B'C + ABC + A'BC' is B'C.